2020
DOI: 10.2306/scienceasia1513-1874.2020.015
|View full text |Cite
|
Sign up to set email alerts
|

The exact solution of the average run length on a modified EWMA control chart for the first-order moving-average process

Abstract: Statistical process control methods are widely used in several fields for monitoring and detecting process problems. One of them is the control chart which is powerful and effective for monitoring many types of processes, and its capability is usually measured using the average run length (ARL). In this article, we investigate explicit formulas for both the one-and the two-sided ARL on a modified exponentially weighted moving-average (EWMA) control chart for a first-order moving-average process with exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The more quickly a control chart detects shifts, the better its performance. The Average Run Length (ARL) is usually used to assess the control charts in the time domain [36]. When the process is in-control, ARL is shown by 0 ARL and for out-of-control conditions, it is shown by 1 ARL .…”
Section: -5-time Domain Constraintmentioning
confidence: 99%
“…The more quickly a control chart detects shifts, the better its performance. The Average Run Length (ARL) is usually used to assess the control charts in the time domain [36]. When the process is in-control, ARL is shown by 0 ARL and for out-of-control conditions, it is shown by 1 ARL .…”
Section: -5-time Domain Constraintmentioning
confidence: 99%
“…Sunthornwat et al [21] found the explicit formula and the optimal parameters to evaluate the ARL for a long-memory ARFIMA process on the EWMA chart. Recently, Supharakonsakun et al [22] presented the exact solution of the ARL on the modified EWMA chart for the MA(1) process. Saghir et al [23] proposed a modified EWMA chart that deduce the existing chart from its special cases.…”
Section: Introductionmentioning
confidence: 99%
“…After that, Peerajit et al [17] studied the NIE method of ARL on CUSUM chart. Supharakonsakun et al [18] evaluated the ARL by NIE method on modified EWMA and compared efficiency with EWMA control chart. Sunthornwat et al [19] derived explicit formulas of ARL on CUSUM chart for seasonal and non-seasonal moving average processes with exogenous variables and evaluated against the NIE method.…”
Section: Introductionmentioning
confidence: 99%